1988
DOI: 10.1111/j.1365-2265.1988.tb01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Response to Metoclopramide Does Not Distinguish Patients With Hypogonadotrophic Hypogonadism From Delayed Puberty

Abstract: The prolactin response to metoclopramide (MCP) was studied in 23 sexually immature males, 14 with isolated hypogonadotrophic hypogonadism (IHH) and nine with constitutional delayed puberty. Six of the 14 IHH patients had not been treated prior to our study, whereas eight had received long term therapy with testosterone or hCG for variable periods ranging from 1 to 20 years. We also measured the prolactin response to chlorpromazine (CPZ) in the untreated IHH men. In these untreated subjects, we observed a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In male patients with hypogonadal hypogonadism, i.e. in cases with low GnRH/gonadotropin levels, in contrast to high releasing hormone concentration in TS, a response has been reported (Cristiano et al, 1988;Gooren et al, 1984). Denef (1985) demonstrated that there are important paracrine interactions between gonadotrophs and lactotrophs and that GnRH stimulates prolactin release proportional to the number of gonatotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…In male patients with hypogonadal hypogonadism, i.e. in cases with low GnRH/gonadotropin levels, in contrast to high releasing hormone concentration in TS, a response has been reported (Cristiano et al, 1988;Gooren et al, 1984). Denef (1985) demonstrated that there are important paracrine interactions between gonadotrophs and lactotrophs and that GnRH stimulates prolactin release proportional to the number of gonatotrophs.…”
Section: Discussionmentioning
confidence: 99%